Persepsi Generasi Z terhadap Praktik Judi Online di Desa Rahuning II, Kabupaten Asahan - Ramadhani, Nazwa; Matondang, Muhammad Alfikri (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Online gambling has increasingly attracted Generation Z due to aggressive promotional strategies and the widespread availability of digital platforms. Beyond entertainment, it offers the allure of quick financial gains, which intensifies participation. This study aims to explore Generation Z’s perceptions of online gambling within a specific local context, highlighting behavioral attitudes and potential risks. Employing a qualitative approach, data were collected through semi-structured interviews and non-participant observations with selected respondents in Rahuning II village, Asahan Regency. Findings reveal that participants generally view online gambling as an inappropriate and ethically questionable activity, associating it with adverse psychological, financial, and social consequences. Respondents emphasized the long-term risks, including addiction, economic instability, and strained interpersonal relationships. These results contribute to the discourse on digital risk behavior among youth, providing insights for policymakers, educators, and community leaders to design targeted interventions and educational campaigns aimed at prevention. This research also enriches theoretical understanding of risk perception in the digital era.